2018
DOI: 10.18203/2349-3291.ijcp20183527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of platelet and its indices as a marker of neonatal sepsis: a prospective case control study

Abstract: Background: Neonatal sepsis is major cause of neonatal morbidity and mortality worldwide. Blood culture and sepsis screening are currently used method, but their utility is limited due to delayed reporting and increased cost. Platelet indices are one such set of parameters which can be helpful in the future diagnosis of neonatal sepsis. This study was aimed to evaluate the significance of platelet indices either alone or in combination with existing sepsis screen as a marker of neonatal sepsis.Methods: Neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
2
16
1
Order By: Relevance
“…Elevated MPV (16) and PDW may be used as a marker for screening of sepsis. Choudhary et al (17) reported that high MPV, high PDW and thrombocytopenia are more common in late onset than early onset sepsis. Although, Shaaban and Safwat (18) found MPV as a marker of early onset sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated MPV (16) and PDW may be used as a marker for screening of sepsis. Choudhary et al (17) reported that high MPV, high PDW and thrombocytopenia are more common in late onset than early onset sepsis. Although, Shaaban and Safwat (18) found MPV as a marker of early onset sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The normal value of MPV was < 10.8 fL and PDW was < 16.8 fL. 1,8 Soon after admission, 3 mL blood specimens were taken and processed for blood culture, total leukocyte count (TLC), micro-ESR, I/T neutrophil ratio, and CRP. Platelet indices (platelet count, MPV, PDW) were also determined with an automated hematology analyzer (SYMEX XN-1000R).…”
Section: Methodsmentioning
confidence: 99%
“…The situation is even more in low income underdeveloped countries. 1 However, neonatal sepsis is a diagnostic challenge, as there are overlapping signs and symptoms which preclude a specific diagnosis of sepsis. 2 Neonates are fragile and can deteriorate rapidly, thus, early diagnosis and prompt treatment is required.…”
mentioning
confidence: 99%
See 2 more Smart Citations